Analysis and Simulation of a Fractional Order Optimal Control Model for HBV. (23rd June 2020) - Yang, Liangli; Su, Yongmei; Li, Xiaoke; Ye, Yongan
Abstract : In this paper, we propose a fractional optimal control model of anti-HBV infection based on saturation incidence and logistic proliferation of uninfected cells for the first time. We derive the basic reproduction number R 0 and the cytotoxic T lymphocyte immune response reproductive number R 1 and give the stable analysis based on R 0 and R 1 . We analyse the optimal control condition and give two optimal control strategies about entecavir monotherapy and combination therapy of traditional Chinese medicine and entecavir with different fractional orders by simulation. The simulation shows that combination therapy may be a good choice in anti-HBV infection therapy. We also compare the objective function values of the optimal control strategies with other constant control strategies; the comparison shows that the optimal therapy can get similar or better treatment effect with less drug dose and side effects.